Myeloid-Related Protein Activity in Rheumatoid Arthritis - Charles J. Malemud (International Journal of Inflammation)
SA100A8, SA100A9, and SA100A12 are members of the myeloid-related protein class. SA100A8 and SA100A9, also known as MRP-8 and MRP-14, respectively, are intracellular Ca2+-binding proteins produced mainly by neutrophils and monocytes where they exist as a heterodimeric complex in the cytosol. The MRP-8/-14 complex has been shown to promote chronic inflammation associated with rheumatoid arthritis (RA). In that regard, MRP-8 and MRP-14 regulate the inflammatory response through their capacity to recruit neutrophils and monocytes to target tissues resulting in attachment to endothelium. MRPs also activate the signal transduction pathway principally involving the stress-activated/mitogen-activated protein kinases. MRP-8/MRP-14 also increased nitric oxide synthesis. Most recently, the MRP-8/MRP-14 complex was shown to be a novel ligand for the toll-like receptors (TLRs) and TLR-4, in particular. Engagement of TLRs by the MRP-8/-14 complex may be particularly important for activating antigen-presenting dendritic cells which regulate critical autoimmune responses that promote chronic synovitis characteristic of RA.